Behavioral decline and premature lethality upon pan-neuronal ferritin overexpression in Drosophila infected with a virulent form of Wolbachia - Kosmidis, Stylianos; Missirlis, Fanis; Botella, Jose A.; Schneuwly, Stephan; Rouault, Tracey A.; Skoulakis, Efthimios M. (Frontiers in Pharmacology, 2014)
Iron is required for organismal growth. Therefore, limiting iron availability may be a key part of the host’s innate immune response to various pathogens, for example in Drosophila infected with Zygomycetes. One way the host can transiently reduce iron bioavailability is by ferritin overexpression. To study the effects of neuronal-specific ferritin overexpression on survival and neurodegeneration we generated flies simultaneously over-expressing transgenes for both ferritin subunits in all neurons. We used two independent recombinant chromosomes bearing UAS-Fer1HCH, UAS-Fer2LCH transgenes and obtained qualitatively different levels of late-onset behavioral and lifespan declines. We subsequently discovered that one parental strain had been infected with a virulent form of the bacterial endosymbiont Wolbachia, causing widespread neuronal apoptosis and premature death. This phenotype was exacerbated by ferritin overexpression and was curable by antibiotic treatment. Neuronal ferritin overexpression in uninfected flies did not cause evident neurodegeneration but resulted in a late-onset behavioral decline, as previously reported for ferritin overexpression in glia. The results suggest that ferritin overexpression in the central nervous system of flies is tolerated well in young individuals with adverse manifestations appearing only late in life or under unrelated pathophysiological conditions.